PENGARUH DOSIS BOKASHI DAUN KRINYU (Chromolaena odorata) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Suhda F Layn; Avia J Matatula; Marlita H Makaruku (JURNAL BUDIDAYA PERTANIAN, 2016)
This study aims to determine bokashi leaves krinyu doses needed to support the growth and mustard greens (Brassica juncea L.) production. This study using the design of random group with the treatment consisting of: without the treatment, dose bokashi leaves krinyu 5 ton/ha, dose bokashi leaves krinyu 10 ton/ha, bokashi leaves krinyu 15 ton/ha, dose bokashi leaves krinyu 20 ton/ha. The results of study show that dose bokashi leaves krinyu 20 ton/ha give results of the highest in all parameters observations namely high plants 29,39 cm, number of leaves 9,63 sheet, broad leaves 72,51 cm2, weight of the root 5,81 g and weight of fresh per plants 193,33 g.